SENSE OF COHERENCE IN STUDENT AGE AS AN INDICATOR OF ADAPTATION AND PSYCHOLOGICAL WELL-BEING (Psychology Travelogs, 2025)
The article explores the sense of coherence as a fundamental psychological construct that plays a crucial role in the adaptation and psychological well-being of university students. Student age represents a sensitive developmental period marked by intensive personal growth, identity formation, increased academic demands, and constant social changes. In such conditions, young people frequently encounter stress, uncertainty, and emotional overload, which heightens the need for stable internal resources that support their psychological balance. The sense of coherence ‒ defined by A. Antonovsky as a combination of comprehensibility, manageability, and meaningfulness ‒ functions as an integrative mechanism that enables students to perceive life events as predictable, structured, and significant. These components collectively support the individual’s ability to maintain emotional stability, regulate behavior, and interpret stressful situations from a constructive perspective.The abstract highlights how a strong sense of coherence contributes to students’ academic adaptation, enhances their motivation, improves emotional self-regulation, and fosters more effective coping strategies when faced with difficulties. Empirical findings from contemporary psychological research indicate that students with higher levels of coherence demonstrate lower vulnerability to anxiety, burnout, and depressive symptoms, while showing greater resilience, cognitive flexibility, and readiness to overcome academic and social challenges. The article also emphasizes the impact of the broader socio-cultural context ‒ particularly the consequences of war, social instability, forced displacement, and changes in learning environments ‒ on the formation and functioning of coherence in student youth.Furthermore, the article summarizes the main socio-psychological determinants influencing the development of the sense of coherence, including personal resources (self-regulation, self-esteem, resilience), interpersonal factors (social support, quality of communication, group belonging), and contextual influences (educational climate, societal uncertainty, cultural norms). The sense of coherence is presented as a key adaptive resource that integrates cognitive, emotional, and motivational processes, enabling young people to maintain psychological well-being, navigate complex life circumstances, and constructively engage in academic and personal development.
Keywords: sense of coherence; student youth; resilience; stress resistance; psychological well-being; adaptation